SYNERGISTIC EFFECT OF GINGER, PROPOLIS ADDED TO CONCENTRATED DIET ON SOME PRODUCTION AND PHYSIOLOGICAL CHARACTERISTICS OF THE AWASSI EWES - AL-jubori, O. S. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was aimed to find out the synergistic effect of ginger and propolis some productivity and physiological traits of Awassi ewes. The study was conducted in field the Department of Animal Production - College of Agriculture, University of Baghdad Al-Jaderia, during 14/01/2016 - 03/27/2016, using 12 Awassi ewes with ages from 9 -11 months old ,average weight of 31 kg, The results showed a significant increase in the glucose for concentration (P <0. 05) in the ginger group compared with other groups where .significant increase in the concentration of blood sugar(81.0 mg / 100 ml of blood) in the first month and continued to the second month,The level of cholesterol increase (65.90) in the second month of the group of ginger, triglycerides, Low-density lipid had significant increase in the group ginger , significant increase in propolis group with high density lipid (54.00) , total protein , albumin and GPT enzyme shows significant increased effect on the contrary GOT enzyme was increased significant in mixture group in the second month (13.00IU / liter), while the level of hemoglobin and the Packed cells volume and the total count of white blood cells and red blood cells did not show any significant differences(normal value ) , It can be conclude from this study that the addition of 25 g ginger to concentrated diet / head / day is the best treatment.